Replanting the tree of life - Leach, David; McConnell, Amanda (Oley, PA : Bullfrog Films, 1987)
A stimulating look at trees and forests from a variety of viewpoints. It acknowledges the importance of trees not only to the environment but also to culture, religion, industry, the economy, and the future
Copy in DVD Format
Executive producers, Heather MacAndrew, David Springbett
Narrator: Murray Cruchley
VHS Format
Keywords: Trees; Forests and forestry -- Environmental aspects